Efetividade de um programa de exercício físico com dupla tarefa nas funções cognitivas e na funcionalidade motora de idosos com doença de Alzheimer - LOPES, Emmanuel Dias de Sousa (2017)
Alzheimer's disease (AD) is the most prevalent form of dementia among the elderly population, characterized by being neurodegenerative, initially insidious and evidenced by the recent memory decline and with evolution it is possible to highlight the commitment of attention, executive functions, language and spatial and temporal orientation. This study aimed to analyze the effectiveness of a dual-task multimodal exercise program on cognitive functions and motor function in elderly patients with mild and moderate AD, before and after 12 weeks, and to compare with their untrained pairs. It was a quasi-experimental study, the sample was composed of 19 elderly patients with AD diagnosis, divided into intervention group (n = 11) with mean age of 75.8 years and control (n = 8) with a mean of 76,1 year, in a mild and moderate stage, of both sexes, aged 60 years and over, living in the municipality of Uberaba. The instruments used for evaluation were: Clinical Dementia Rating Score (CDR), Mini-Mental State Examination (MMSE), Frontal Evaluation Battery (BAF), Clock Drawing Test (TDR), Verbal Fluency Test Semantics (TFVS), Short Physical Performance Battery (SPPB). The intervention was carried out through exercises with stimulating the various physical capacities, such as muscular strengthening, balance, agility, motor coordination and double task. Each class lasted 60 minutes, held three times a week, on non-consecutive days and with a total duration of 12 weeks. Regarding the classification of the degree of commitment of the elderly with AD, according to the CDR, the two groups presented similar values, intervention group 1.44 points and control group 1.37 points. Repeated measures ANOVA indicated interaction between groups and moments, for the variables: MMSE, BAF and gait. MMSE (total score) in the intervention group (pre: 18.64 ± 4.7 points, post: 19.82 ± 4.8 points) and also in the control group (pre: 17.0 ± 7.3 points, post: 19.6 ± 6.0 points) with significant difference (p = 0.017) between groups and moments. For BAF, there were significant differences (p = 0.005) in both groups, intervention group (pre: 9.36 ± 2.5 points, post: 10.91 ± 3.8 points) and control group (pre: 9, 5 ± 4.3 points, powders: 11.63 ± 2.9 points). For the TDR, there was no difference between10 the groups (p = 0.931), the same occurred with the TFVS (p = 0.942). The SPPB overall score (p = 0.849), the static balance test (p = 0.966) and the chair lift and sit test (p = 0.9960) showed no differences between groups, behavior other than the speed test of gait, which presented a significant difference (p = 0.050) in the intervention group. Multimodal physical exercise with dual tasks can promote improvements in global cognitive functions, executive functions and motor functionality related to the gait speed of the elderly with AD.